ANALISIS PENGGUNAAN BAHASA PADA MEDIA LUAR RUANG DI KOTA SINGKAWANG - Sari, Nilam; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The Research on the use of language on outdoor media in Singkawang City focuses on the physical variables, language variables, legal variables, and criteria of language situations in accordance with the formulation of problems related to research purposes that is to describe the use of language on outdoor media in Singkawang City based on physical variables and legal variables, describe the analysis of language usage on outdoor media in Singkawang City based on language variable, and describe the criteria of language situation of language use on outdoor media in Singkawang City based on assessment instrument. Data that can be collected amounted to 192 data. The data are grouped into 7 groups of monitoring objects and described in general. After that, the data is classified into 5 research objects and analyzed based on the formulation of the problem. Based on the results of data analysis of outdoor media in Singkawang get score 245,3.This result determines that Singkawang City is included in a controlled area criterion III, areas where the use of foreign languages is sufficiently under control, with more priority on the use of Indonesian language or the preservation of regional languages. Keywords: Outdoor Media, Physical Variables, Language Variables, Legal  Variables, Singkawang City.   Top of Form